Evaluasi Kritis dan Model Alternatif Hunter Curves untuk Sistem Plumbing Gedung Bertingkat di Medan - Zufri Hasrudy Siregar; Arif Fadillah Nasution; Mawardi Mawardi; Refiza Refiza; Suherman Suherman (universitas teuku umar, 2025)
Clean water is a fundamental necessity in high-rise buildings, so calculating peak water demand is a critical aspect of plumbing system design. So far, planners in Indonesia still rely on Hunter Curves (1940), a classic method developed in the United States and has been used for more than eight decades. The Hunter method is no longer relevant because water consumption patterns have changed, the use of water-saving devices is becoming more widespread, and the characteristics of tropical buildings in Indonesia are different from Hunter's basic assumptions. This study critically evaluates Hunter Curves through a case study of the Lexington Tower Medan Healthcare Building (20 floors, 160 units), comparing the Hunter method with an alternative model based on a locally calibrated Monte Carlo probabilistic simulation (P95). Monte Carlo simulations were performed in 10,000 iterations using MATLAB-based stochastic modeling to obtain peak discharge distributions. The results showed a peak discharge according to Hunter of 34,695 L/s, while the alternative model reached 37,440 L/s (+7.91%). This difference affects the pipe dimensions and pump power, but the additional energy cost (±Rp850,000/year) is commensurate with the increased reliability of the system. This study confirms that Hunter Curves are obsolete and need to be replaced by a more accurate, energy-efficient, and sustainable approach